Ảnh hưởng của xử lý nhiệt tới các tính chất của lớp mạ NiP điện hóa - Liêm, Lê Thanh; Dương, Trịnh Hồng; Bích Thủy, Hoàng Thị (Vietnam Journal of Chemistry, 2017)
Electroplating NiP coatings are used on metallic components to enhance their hardness, wear resistance, corrosion resistance, and durability. Further improvement in properties can be obtained by heat treatments at various temperatures. This paper deals with electroplating NiP coatings which are heat treated at various temperature. The properties of coatings were investigated such as microhardness, wear resistance and corrosion resistance. The morphology and structural properties of the coatings were analyzed by optical microscope and X-ray diffraction (XRD) measurements. The Vickers hardness tests were performed on the surface of the NiP coatings. Taber Abraser tests were used to assess their wear resistance. The corrosion resistance of the samples was investigated through potentiodynamic polarization curves, electrochemical impedance spectroscopy (EIS), salt spray testing. It is indicated that heat treatments have a positive influence on properties of electroplating NiP coatings. Keywords. Electrodeposition, NiP alloy, Hard nickel film, Corrosion, Electroplating.